2016
DOI: 10.1017/s1368980016001567
|View full text |Cite
|
Sign up to set email alerts
|

Violations of the International Code of Marketing of Breast-milk Substitutes: Indonesia context

Abstract: Objectives: To measure compliance with the International Code of Marketing of Breast-milk Substitutes ('the Code') in Indonesia. Design: The study was a cross-sectional survey using the Interagency Group on Breastfeeding Monitoring protocol. Setting: Public and private health facilities in six provinces on Java island in Indonesia. Subjects: A total of 874 women (382 pregnant women and 492 breast-feeding mothers of infants below 6 months) and seventy-seven health workers were recruited from eighteen participat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
22
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 17 publications
9
22
1
2
Order By: Relevance
“…A study found that health workers, breast-milk substitute manufactures, and company representatives were guilty of violations of the WHO CODE and recommended a regular monitoring system to ensure compliance and enforcement of WHO CODE. The same study also confirms that health workers and representatives of breast-milk substitutes companies in Indonesia are working together (Hidayana Et al., 2017). Infant formula and other breast-milk substitutes are latent threats for breast-milk supporters in Indonesia.…”
Section: Introductionsupporting
confidence: 77%
“…A study found that health workers, breast-milk substitute manufactures, and company representatives were guilty of violations of the WHO CODE and recommended a regular monitoring system to ensure compliance and enforcement of WHO CODE. The same study also confirms that health workers and representatives of breast-milk substitutes companies in Indonesia are working together (Hidayana Et al., 2017). Infant formula and other breast-milk substitutes are latent threats for breast-milk supporters in Indonesia.…”
Section: Introductionsupporting
confidence: 77%
“…The ease of infant formula access; aggressive marketing in retail outlets and the media; continued provision of formula samples and feeding supplies by health professionals; and lack of comprehensive understandings of optimal infant nutrition and feeding practices, are some of the reasons that families choose to use infant formula [13,24]. Violations of the Code by infant formula companies include incentivizing the provision of infant formula and feeding supplies by health professionals and retail outlets, and producing misleading advertisements and product labelling [25]. In the US, the government formed the National Alliance for Breastfeeding Advocacy (NABA) to monitor compliance with the Code and establish a task force to identify hospitals which have collaborated with infant formula companies [50].…”
Section: Previous Studiesmentioning
confidence: 99%
“…Thus, no fines nor sanctions can be given to infant formula companies that collaborate with community-based workers. Moreover, Hidayana et al [25] reported that some health workers received gifts from infant formula companies, infant formula labelling contained content that discouraged breastfeeding practice, and free formula samples were being distributed to mothers. In the case of the BFHI, in 2015 just 8% of hospitals in Indonesia had been designated as BFHI [26].…”
Section: Introductionmentioning
confidence: 99%
“…Promotion and consumption of these products have increased in step with global sales volume (Kent, 2015). Marketing of BMS within the health care system undermines mothers' confidence in breastfeeding (Parry, Ip, Chau, Wu, & Tarrant, 2013) and has been observed across South and Southeast Asia even when national legislation is in place to limit it (Barennes, Slesak, Goyet, Aaron, & Srour, 2016;Durako, Diallo, Thompson, & Aronson, 2016a;Durako, Diallo, Thompson, & Aronson, 2016b;Hidayana et al, 2016;Sobel et al, 2011). Prior research has shown that early use of BMS for feeding of newborns can increase the likelihood of continued BMS use for infant feeding and contribute to early breastfeeding cessation (Onah et al, 2014;Patil et al, 2015;Raheem, Binns, Chih, & Sauer, 2014).…”
mentioning
confidence: 99%